Answer:
y = f(x) = ( x + 4 )( x - 1 )( x - 3 )
Explanation:
Let the equation of the curve drawn on the graph is y = f(x)
We have to find an expression for f(x).
If we take y = 0, then there will be three values of x which are -4, 1 and 3.
Since, there is three solutions of f(x) = 0, hence, f(x) will be a three degree polynomial. and ( x + 4 ), ( x - 1 ) and ( x - 3 ) will be the three factor of the equation.
Therefore, y = f(x) = ( x + 4 )( x - 1 )( x - 3 ) is the required equation of the graph. (Answer)